E-commerce and green food consumption of rural residents: implications for sustainable rural food systems - Qiu, Hailan; Zhang, Xueyi; Deng, Hanyun; Wu, Xiangqi; Wu, Zhihua; Sheng, Biao (Frontiers in Nutrition, 2025)
IntroductionE-commerce is a powerful tool for promoting the green food consumption in rural areas. It can effectively break through the shackles of poor information flow, low income and traditional consumption patterns. This study explores the impact of e-commerce operations on green food consumption of rural residents, focusing on its role in enhancing information access, improving income, and upgrading logistics. It provides a new theoretical support for promoting green food consumption and ensuring food safety.MethodsBased on survey data from 2,805 rural residents across 10 provinces in China, this study employs a binary Probit model and a mediating effect model to examine the impact and mechanisms of e-commerce operations on green food consumption of rural residents, while also testing for heterogeneous effects. Furthermore, it investigates the differential influences of e-commerce operation models, operation scales, product types, and types of green food.Results and discussionThe findings indicate that e-commerce operations significantly promote green food consumption of rural residents, and this conclusion remains robust after multiple robustness and endogeneity tests. Mechanism analysis reveals that e-commerce facilitates green food consumption by improving household income, enhancing information acquisition, and strengthening logistics infrastructure. Heterogeneity analysis shows that the positive effect is more pronounced among rural residents with higher social capital, in the central and eastern regions, and in major grain-producing areas. Additional results suggest that platform e-commerce, large-scale operations, and businesses involving primary processed products exert stronger effects on green food consumption, while e-commerce operations more effectively boost the consumption of green vegetables and dairy products. Overall, by examining e-commerce operations, this study provides an in-depth analysis of how online market participation fosters green food consumption of rural residents, offering important insights for advancing sustainable consumption in the context of digital economy transformation.